The relationship of the lipoxygenase enzyme in female blood with cardiovascular diseases - Amira Mahmoud; Rawia Rashed (College of Education for Pure Sciences, 2013)
ABSTRACT   Lipoxygenase , LOX, is one of the enzymes that  affect the lipid metabolism. On the other hand, lipids can influence the risk of cardiovascular diseases and diabetes. Therefore, the present study deals with the estimation of the level of LOX in blood of females with cardiovascular disease ( only/ or in addition to diabetes). The study also focused on assessing the serum total cholesterol (TC), high density lipoprotein cholesterol (HDL-C)، glutathione (GSH) and malondialdehyde (MDA). The results showed that the incidence of cardiovascular disease and diabetes led to a significant increase in the level of LOX in both the blood-cells homogenate and the serum. Also, the results indicated that there was a significant increase in the level of TC and MDA and there was a significant  decrease in the level of HDL-C and GSH in addition to an increase in the ratio of TC/HDL-C. On the basis of the results, it may be concluded that the high level of LOX, TC و MDA and TC/HDL-C ratio and the low level of HDL-C, GSH are  considered as a negative indicators that promotes cardiovascular disease and diabetes.